2020
DOI: 10.1007/s00431-020-03667-8
|View full text |Cite
|
Sign up to set email alerts
|

Sleep problems increase the risk of musculoskeletal pain in boys but not girls: a prospective cohort study

Abstract: Adults with sleep problems are at higher risk for onset of musculoskeletal pain, but the evidence is less clear for children. This prospective cohort study investigated whether children with sleep problems are at higher risk for onset of musculoskeletal pain and explored whether sex is a modifier of this association. In a prospective cohort study of Australian schoolchildren (n = 1239, mean age 9 years), the associations between sleep problems at baseline and new onset of both musculoskeletal pain and persiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…Musculoskeletal pain was common in this cohort (> 40%), in agreement with findings of other cohorts that used similar pain assessment methods [ 39 ]. Whilst previous research has shown mixed effects of psychological symptoms on later adolescent musculoskeletal pain [ 14 20 ], there is support for the current findings.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Musculoskeletal pain was common in this cohort (> 40%), in agreement with findings of other cohorts that used similar pain assessment methods [ 39 ]. Whilst previous research has shown mixed effects of psychological symptoms on later adolescent musculoskeletal pain [ 14 20 ], there is support for the current findings.…”
Section: Discussionsupporting
confidence: 90%
“…Potential bias due to missing data was assessed by inspecting the percentage of missingness for each variable, and missing data were replaced through a chained equation multiple imputation method in order to maximize statistical power and increase precision (i.e. to limit the possibility of a biased estimate) [37,38]. All raw variables used in the analysis (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, 50–60% of adolescents with chronic pain problems report sleep deficiency [ 17 ]. The relationship between sleep deficiency and chronic pain has often been described as bi-directional, although evidence suggests that sleep is a stronger predictor of pain rather than vice versa [ 19 , 20 , 21 ]. However, despite this knowledge, sleep disturbance is not included in existing conceptual models of acute to chronic pain transition.…”
Section: Introductionmentioning
confidence: 99%